Ensuring food security and competitiveness of the agro-industrial complex - Aigul Jumabayeva; Meiramkul Tuleubayeva; Dina Kanagatova; Kymbat Kunanbayeva; Аruana Sekerova (Brazilian Journal of Food Technology, 2023)
Abstract The formation of the Kazakh national agricultural market is complicated by a sharp decline in government assistance to the country's agricultural sector, a decrease in the effectiveness of its regulation, a violation of economic relations between market entities, a drop in effective demand of the population, the disintegration of the economic space of the Commonwealth of Independent States countries, an increase in food imports. The presented study is aimed at considering the regulation of processes and the security of the grocery market and the support by the state of Kazakhstan for its own agro-industrial complex. The following research methods were applied in the study: analysis and synthesis of information, parsing of literature data on the subject of the study, and classification of information and data. The paper discussed the issues of regulating the development and safety of the food market and state aid for the agricultural industry of the republic. Local and international food security was thoroughly studied as a mechanism of national security. In addition, the basic principles were determined of guaranteed supply of the population with necessary foodstuffs at the national level, and food safety in a globalizing world, which has aroused special interest in the research on the competitiveness in the agricultural sector and its management system. The competitive ability of agricultural products from the perspective of economists is the ability to compete on price terms and quality parameters while ensuring steady growth in sales volumes in the internal and external markets. The agro-industrial complex is an important segment of diversification. This research is of practical value for scientists who work and conduct scientific activities in the fields of public catering, agriculture, and the food industry.